2021
DOI: 10.34067/kid.0004642020
|View full text |Cite
|
Sign up to set email alerts
|

A Hyaluronan Synthesis Inhibitor Delays the Progression of Diabetic Kidney Disease in A Mouse Experimental Model

Abstract: Background: The role of hyaluronan (HA) in the development and progression of diabetic kidney disease (DKD), as well as the precise mechanisms and consequences of HA involvement in this pathology are still to be clarified. Methods: In this study, we assayed the effects of the HA synthesis inhibitor 4-methylumbelliferone (4-MU) on the development of DKD. Diabetic type 2 model mice (eNOS-/- C57BLKS/Jdb) were fed artificial diets containing 5% 4-MU or not for 9 weeks. Plasma glucose, glomerular filtration rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…42,46 Our study has shown the benefits of 4-MU, a HA synthesis inhibitor, in slowing DKD progression in animal experimental models with potential important benefit in glucose control. 3 Phase 1 study on 4-MU among healthy human adults has been completed and published, highlighting its safety and tolerabiltiy. 59 On the basis of all of this in addition to the results of other in-human published studies, we believe that it is time for a phase 2 in-human study to evaluate the safety and efficacy of using 4-MU among patients with DKD.…”
Section: Global Availability Of 4-mu At Presentmentioning
confidence: 99%
See 4 more Smart Citations
“…42,46 Our study has shown the benefits of 4-MU, a HA synthesis inhibitor, in slowing DKD progression in animal experimental models with potential important benefit in glucose control. 3 Phase 1 study on 4-MU among healthy human adults has been completed and published, highlighting its safety and tolerabiltiy. 59 On the basis of all of this in addition to the results of other in-human published studies, we believe that it is time for a phase 2 in-human study to evaluate the safety and efficacy of using 4-MU among patients with DKD.…”
Section: Global Availability Of 4-mu At Presentmentioning
confidence: 99%
“… 40 , 41 This increased renal HA accumulation has been linked to worsened proteinuria, faster loss of kidney function, and increased cardiovascular events. 3 , 41 , 42 Afferent and efferent AH is one of the key pathologic findings in DKD. 5 There have been various pathologic classifications of AH on the basis of the number of arterioles affected, such as the criteria proposed by Tervaert et al , 43 or the wall thickness and percentage of luminal area occlusions in the most severely affected arteriole 44 or the number of arterioles affected and the circumferences of the arterioles involved, as in the Banff lesion score.…”
Section: Ha and Kidney Diseasementioning
confidence: 99%
See 3 more Smart Citations